EVALUASI PELATIHAN MANAJEMEN ASFIKSIA BAYI BARU LAHIR UNTUK BIDAN DI KOTA PALANGKA RAYA - , Ina Indra Yanti; , Prof. dr. Muhamad Hakimi, Sp.OG(K), Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: In the world Newborn asphyxia is one of the major causes of perinatal mortality in both developed and developing countries. Each year, approximately 3% (3.6 million) of 120 million infants are born asphyxiated